VD_FINDINFO Jug / 2012 / 132 vom 16. Februar 1969 - VD Tribunal cantonal (1969)
RESPONSABILITÉ RESTREINTEDROIT PÉNAL, ATTÉNUATION DE LA PEINE, PEINE | 19 al. 2 CP, 191 CP, 40 CP, 47 CP, 48a CP, 49 CP, 19a ch. 1 LStup